Impact of School Population Composition, Workload, and Teachers’ Utility Values on Teaching Quality: Insights From the Dutch TALIS-2018 Data - Ouwehand, Kim H. R.; Xu, Kate M.; Meeuwisse, Marieke; Severiens, Sabine E.; Wijnia, Lisette (Frontiers in Education, 2022)
Several studies show that teaching quality is an important predictor of students’ academic achievement. However, less is known about factors that are important for teaching quality. In the present study, it was hypothesized that school population composition (i.e., students’ socioeconomic status [SES] and migration background), workload, and teachers’ utility values toward teaching were important factors related to their teaching quality. The Dutch Teaching and Learning International Survey (TALIS) 2018 was explored (N = 1884, secondary school teachers and 116 school leaders) to test our hypotheses. Data gathering followed a two-step procedure. Firstly, 200 schools were randomly selected. Secondly, 20 teachers within each school were randomly selected. Multi-item scales operationalized teaching quality on teachers’ self-reported classroom management, cognitive activation, clarity of instruction, and positive student-teacher relationships. Multilevel analyses showed that teachers’ social utility value was positively associated with all dimensions of teaching quality, whereas personal utility value was only associated with classroom management and clarity of instruction. Teachers working at schools with moderate shares of students from a socioeconomically disadvantaged background reported higher clarity of instruction (β = .42), and moderate and high shares report lower cognitive activation (β = -.40, β = -.33 respectively) than those working at schools with low shares. Student-teacher relationships were rated more positively by teachers working at schools that reported no students with a migrant background than those working at schools with a small share (β = .33). Moreover, teachers working at schools with high shares of students with migration backgrounds (β = -.17) reported more negative relationships. These results suggest that dealing with low SES at schools affects the cognitively-focused elements of teaching quality, while dealing with students with a migration background seems to affect the social teaching qualities of teachers.